THE KINETIC METHOD OF AN ASSESMENT OF JET FUELS CHEMICAL STABILITY - L. A. Vlasenkova; K. V. Shatalov; S. V. Shishaev (Научный вестник МГТУ ГА)
The need of studying of jet fuels chemical stability incorporating a hydrogenation component is required. The kinetic method of an assessment of chemical stability of jet fuels is offered.